2004
DOI: 10.1186/1472-6815-4-2
|View full text |Cite
|
Sign up to set email alerts
|

Readmission and overstay after day case nasal surgery

Abstract: BackgroundA readmission is classified as a patient necessitating readmission to hospital due to a post-operative complication following discharge. An overstay however, is classified as a patient having to stay longer than the planned duration in hospital (not having been discharged in the interim) due to a post-operative complication. This study aims to investigate patient-related factors that predispose to readmission or overstay and thus make recommendations to decrease the likelihood of readmission or overs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 8 publications
1
20
1
Order By: Relevance
“…The leading causes for these events included postoperative pain and bleeding. Similarly, Singh et al 2 reported that 24% of patients had unacceptable levels of postoperative pain, delaying their hospital discharge. In our study, the VAS pain scores in the lidocaine group were very low throughout the 24-h study period, and no patient required rescue analgesia.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The leading causes for these events included postoperative pain and bleeding. Similarly, Singh et al 2 reported that 24% of patients had unacceptable levels of postoperative pain, delaying their hospital discharge. In our study, the VAS pain scores in the lidocaine group were very low throughout the 24-h study period, and no patient required rescue analgesia.…”
Section: Discussionmentioning
confidence: 97%
“…1 The leading causes of hospital readmission and/or overstay after day-care septorhinoplasty surgery are epistaxis and a high level of postoperative pain. 2 A multimodal analgesia regimen can be used, but many patients suffer from adverse events after opioid administration. 3,4 Also, the use of high doses of nonsteroidal anti-inflammatory drugs is associated with patient readmission after septorhinoplasty surgery.…”
Section: Résumémentioning
confidence: 99%
“…First, pain is the most important cause for delayed return to normal daily activities and work after routine ENT surgery 4 . Second, postoperative pain is an important cause for readmission after day‐case nasal surgery 5 . Third, ESS is commonly performed on a day‐case basis, which needs to be based on an effective and feasible pain treatment regimen, because after discharge patients themselves are responsible for their own pain management.…”
Section: Introductionmentioning
confidence: 99%
“…4 Second, postoperative pain is an important cause for readmission after day-case nasal surgery. 5 Third, ESS is commonly performed on a day-case basis, which needs to be based on an effective and feasible pain treatment regimen, because after discharge patients themselves are responsible for their own pain management. Finally, untreated pain can cause avoidable expenditures to the patients and their employers, and to the health care system.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, recent years have witnessed renewed interest in delineating optimal perioperative analgesic regimens, as the possibility of pain has been cited as a potential barrier for the decision to proceed with surgery . Moreover, there has been increased cognizance of the role prescription drugs play in the opioid “crisis” and the deleterious impact insufficient pain control may have on healthcare costs, as inadequate analgesia may lead to readmission after nasal surgery . In our contemporary healthcare environment, typified by increasing recognition of the impact of interventions on healthcare utilization, evidence‐based reviews provide important clinical guidance.…”
mentioning
confidence: 99%